Kritik Teks atas Luk 11:2: “Πάτερ, ἁγιασθήτω τὸ ὄνομά σου” atau “Πάτερ ἡμῶν ὁ ἐν τοῖς οὐρανοῖς”? - Ngoranubun, Willem (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2021)
Penelitian terhadap manuskrip-manuskrip dari Luk 11:2-4 menunjukkan adanya varian-varian dari Luk 11:2 yang sangat mirip dengan Mat 6:9. Tuhan kita sebenarnya mengajarkan “Πάτερ, ἁγιασθήτω τὸ ὄνομά σου” (Bapa, dikuduskanlah nama-Mu), atau “Πάτερ ἡμῶν ὁ ἐν τοῖς οὐρανοῖς” (Bapa kami, yang ada di surga)? Dengan melalui tahapan-tahapan kritik teks, tulisan ini dibuat untuk menjelaskan bahwa Mat 6:9 menjadi “variant-source” bagi varian Luk 11:2 yang merupakan hasil harmonisasi teks oleh ahli kitab. A study of some manuscripts of Luke 11:2-4 shows that there are variants of Luke 11:2 which are very similar to Matt. 6:9. Did our Lord actually teach, “Πάτερ, ἁγιασθήτω τὸ ὄνομά σου” (Father, hallowed be Your name), or “Πάτερ ἡμῶν ὁ ἐν τοῖς οὐρανοῖς” (Our Father, who is in heaven)? By perusing the stages of textual criticism, this article intends to explain that Mat 6:9 is a "variant-source" for the variant of Luke 11:2 which is the result of the harmonization of texts compiled by the scribes.